THE ROLE OF DIGITAL INTELLIGENCE AND ITS COMPONENTS IN MODERN SOCIETY (Education in the 21st Century, 2023)
The article highlights the essence of the components of digital personal intelligence, which largely determines the effectiveness of human activity in the modern world.It is noted that digital intelligence in humans today is a necessity, as modern learning models will become effective only if there is a sufficient level of mastery of digital technologies by all participants in the educational process, the ability to build effective relationships in the digital space. The essence of digital intelligence (DQ), its components (digital memory, digital empathy and digital footprint) and their place in the modern educational environment have been represented.The concept of digital empathy and its significance in the organization of the educational process in the context of online learning have been revealed. It is indicated that the manifestation of empathy in the online environment is more complex than in face-to-face communication.Some strategies that help the speaker to evoke emotions are described: feeling and understanding of the target audience, instructing students to master the material, colours, emotions, words, maintaining regular online communication, chatting and active listening.It is emphasized that the concept of digital emotional memory is associated with digital empathy, as the mastery of information and digital technologies is accompanied by a significant emotional colour. The concept of "digital footprint" is revealed as information that remains as a result of the user’s work in the network, as well as "digital memories", which are based on emotional contact with digital objects and enhance learning motivation by creating a situation of success.It is concluded that in the context of global digitalization of the modern world, the presence of advanced41digital intelligence and its components is a necessity for each individual, and the general formula of a modern successful personality is a harmonious combination of cognitive, emotional and digital intelligences.
Keywords: digital personality intelligence, digital memory, digital empathy, digital footprint, digital competencies, digitalization of education.